THE EFFECT OF PROFITABILITY, LEVERAGE, SOLVABILITY ON CARBON EMISSION DISCLOSURE WITH COMPANY SIZE AS A MODERATING VARIABLE - Sri Komariyah; Maylia Pramono Sari (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Disclosure emission carbon become element important in accountability companies , especially in the sector contributing energy​ big to emission national research​ This analyze influence profitability , leverage, and solvency to disclosure emission carbon with consider size company as variables moderation and performance environment as variables Control . The results of the 2021–2024 data analysis show that profitability has a significant negative effect, while leverage and solvency have no effect. Company size weakens the effects of profitability and solvency, and strengthens the effect of leverage, although not as hypothesized. These findings suggest that carbon emission disclosure is driven more by external pressure and the need for legitimacy than by a company's financial characteristics.